Skin metastases of lung cancer - Triller Vadnal, Katja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Skin metastases of lung cancer are rare. In over a 3-year period we found only14 cases of skin metastases among 1,614 patients with lung cancer admittedto the University Clinic of Respiratory and Allergic Diseases in Golnik. The metastases are usually manifested on the skin of the chest. Skin metastases are symptoms of progressive disease, and usually a sign of a poor prognosis. The median survival time of lung cancer patients with skin metastases was 85 days from the time of detection of the skin lesion. Because skin metastases can be the first sign of the disease, the entire skin should be carefully inspected whenever malignant disease is suspected.
Keywords: koža; Kožne novotvorbe; Lung Neoplasms; metastaze; Neoplasm Metastasis; Novotvorba, metastaza; Pljučne novotvorbe; pljučni rak; Preživetje, analiza; Secondary; Skin Neoplasms; Survival Analysis